Electroencephalogram Access for Emotion Recognition Based on a Deep Hybrid Network - Zhong, Qinghua; Zhu, Yongsheng; Cai, Dongli; Xiao, Luwei; Zhang, Han (Frontiers in Human Neuroscience, 2020)
In human-computer interaction (HCI), electroencephalogram (EEG) access for an automatic emotion recognition is an effective way for brain robots to perceive human behavior. In order to improve the accuracy of the emotion recognition, a method of EEG access for emotion recognition based on deep hybrid network was proposed in this paper. Firstly, the collected EEG was decomposed into four frequency band signals, and the multiscale sample entropy (MSE) features of each frequency band were extracted. Secondly, the constructed 3D MSE feature matrices were fed into the deep hybrid network for autonomous learning, and the deep hybrid network was composed of continuous convolutional neural network (CNN) and hidden Markov models (HMMs). Lastly, HMMs trained with multiple observation sequences were used to replace the artificial neural network classifier in the CNN, and the emotion recognition task was completed by HMM classifiers. The proposed method was applied to DEAP dataset for emotion recognition experiments, and the average accuracy could achieve 79.77% on arousal, 83.09% on valence and 81.83% on dominance. Compared with the latest related methods, the accuracy was improved by 0.99% on valence and 14.58% on dominance, which verified the effectiveness of the proposed method.